Entrepreneurial Knowledge, Motivation, and Discipline as Determinants of MSME Business Success: Evidence from Coffee Shops in Pemalang, Indonesia - Putra Arifyansyah, Reyza; Shiratina, Aldina (Jurnal MS, 2025)
Objective: This study examines the influence of entrepreneurial knowledge, entrepreneurial motivation, and entrepreneurial discipline on the business success of coffee shop MSMEs in Pemalang, Brebes, and Pekalongan, highlighting the role of behavioral and cognitive factors in sustaining competitive advantage. Methodology: A quantitative survey design was employed involving 212 coffee shop owners as respondents. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS to assess both individual and joint effects of the independent variables on business success. Findings: The results indicate that entrepreneurial knowledge, motivation, and discipline each have positive and significant effects on the success of coffee shop MSMEs. Entrepreneurial knowledge enhances decision-making, marketing, and resource management. Motivation drives persistence, enthusiasm, and resilience in facing challenges. Discipline emerges as the most dominant factor, ensuring consistency, adherence to operational standards, and service quality. Conclusion: Entrepreneurial knowledge, motivation, and discipline collectively serve as complementary drivers of MSME success. Theoretically, this study contributes to entrepreneurship and organizational behavior literature by positioning discipline as a critical determinant of business success. Practically, the findings suggest that MSME practitioners and policymakers should emphasize strengthening knowledge, motivation, and especially discipline to enhance performance, resilience, and long-term sustainability. Keyword : Business Success; Entrepreneurial Knowledge; Entrepreneurial Motivation, and Entrepreneurial Discipline.